2017
DOI: 10.1111/hex.12530
|View full text |Cite
|
Sign up to set email alerts
|

Beyond the consultation room: Proposals to approach health promotion in primary care according to health‐care users, key community informants and primary care centre workers

Abstract: BackgroundPrimary health care (PHC) is the ideal setting to provide integrated services centred on the person and to implement health promotion (HP) activities.ObjectiveTo identify proposals to approach HP in the context of primary care according to health‐care users aged 45‐75 years, key community informants and primary care centre (PCC) workers.MethodsDescriptive‐interpretive qualitative research with 276 participants from 14 PCC of seven Spanish regions. A theoretical sampling was used for selection. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Our findings showed that being respected, acknowledged and having a trustworthy relationship with the professionals were considered a prerequisite for the service users’ involvement in changing their health behaviour. This in line with other studies showing that user involvement is facilitated by a personal relationship, based on respect, collaboration and knowledge sharing . Similarly, Følling and colleagues found that HLC participants emphasized emotional support as essential to give them the courage to start and continue with healthy behaviour changes .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings showed that being respected, acknowledged and having a trustworthy relationship with the professionals were considered a prerequisite for the service users’ involvement in changing their health behaviour. This in line with other studies showing that user involvement is facilitated by a personal relationship, based on respect, collaboration and knowledge sharing . Similarly, Følling and colleagues found that HLC participants emphasized emotional support as essential to give them the courage to start and continue with healthy behaviour changes .…”
Section: Discussionsupporting
confidence: 86%
“…Because involvement of the service users is considered as essential in health promotion initiatives that encourage health behaviour change and aim to enable people to increase control over their health, it is important to address the service users’ own experiences of involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Part of policy development involves decentralizing health‐promoting services from specialist care to primary care . It has previously been shown that it is difficult for primary care practitioners to focus on health promotion . One study suggests that health professionals strive to integrate the ideals of promotion, such as well‐being, but instead tend to focus on adherence to and compliance with medical advice .…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been shown that it is difficult for primary care practitioners to focus on health promotion . One study suggests that health professionals strive to integrate the ideals of promotion, such as well‐being, but instead tend to focus on adherence to and compliance with medical advice . By focusing strictly on risk and disease prevention, health professionals often fail to broaden their aim towards more holistically inclusive and general health promotion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation